The relative efficiency of shipping companies - Lambertides, Neophytos; Panayides, Photis; Savva, Christos S. (My University, 2011)
This paper contributes to the maritime transport literature by examining the relative efficiency of firms in the three key sectors of the shipping industry, i.e. dry, wet and container shipping. Two relative efficiency models are developed to assess relative market and relative operating performance efficiency. The theoretical framework of fundamental analysis is adopted to derive the inputs and outputs in the efficiency models which are assessed using data envelopment and stochastic frontier analysis. Shipping companies were found to exhibit average market efficiency. Market and operating performance efficiency of maritime firms is not consistent. Tanker companies are more market efficient whereas container shipping firms are found to have high operating performance efficiency but were market inefficient. Dry bulk firms were found to have the lowest ratings of market efficiency
Keywords: Fundamental analysis; Relative efficiency; Shipping firms